Inhibition of RhoA/Rho-kinase pathway suppresses the expression of extracellular matrix induced by CTGF or TGF- β in ARPE-19 - Jing Zhu (International Journal of Ophthalmology, 2013)
AIM: To investigate the role of Rho-associated protein kinase (ROCK) inhibitor, Y27632, in mediating the production of extracellular matrix (ECM) components including fibronectin, matrix metallo-proteinase-2 (MMP-2) and type I collagen as induced by connective tissue growth factor (CTGF) or transforming growth factor-β (TGF-β) in a human retinal pigment epithelial cell line, ARPE-19.METHODS: The effect of Y27632 on the CTGF or TGF-β induced phenotype in ARPE-19 cells was measured with immunocytochemistry as the change in F-actin. ARPE-19 cells were treated with CTGF (1, 10, 100ng/mL) and TGF-β (10ng/mL) in serum free media, and analyzed for fibronectin, laminin, and MMP-2 and type I collagen by RT-qPCR and immunocytochemistry. Cells were also pretreated with an ROCK inhibitor, Y27632, to analyze the signaling contributing to ECM production.RESULTS: Treatment of ARPE-19 cells in culture with TGF-β or CTGF induced an ECM change from a cobblestone morphology to a more elongated swirl pattern indicating a mesenchymal phenotype. RT-qPCR analysis and different gene expression analysis demonstrated an upregulation in expression of genes associated with cytoskeletal structure and motility. CTGF or TGF-β significantly increased expression of fibronectin mRNA (P=0.006, P=0.003 respectively), laminin mRNA (P=0.006, P=0.005), MMP-2 mRNA (P= 0.006, P= 0.001), COL1A1 mRNA (P=0.001, P=0.001), COL1A2 mRNA (P=0.001, P=0.001). Preincubation of ARPE-19 with Y27632 (10mmol/L) significantly prevented CTGF or TGF- β induced fibronectin (P=0.005, P=0.003 respectively), MMP-2 (P= 0.003, P=0.002), COL1A1 (P=0.006, P=0.003), and COL1A2 (P=0.006, P=0.004) gene expression, but not laminin (P=0.375, P=0.516)#$NLCONCLUSION: Our study demonstrated that both TGF-β and CTGF upregulate the expression of ECM components including fibronectin, laminin, MMP-2 and type I collagen by activating the RhoA/ROCK signaling pathway. During this process, ARPE-19 cells were shown to change from an epithelial to a mesenchymal phenotype in vitro. Y27632, a ROCK inhibitor, inhibited the transcription of fibronectin, MMP-2 and type I collagen, but not laminin. The data from our work suggest a role for CTGF as a profibrotic mediator. Inhibiting the RhoA/ROCK pathway represents a potential target to prevent the fibrosis of RPE cells. This might lead to a novel therapeutic approach to preventing the onset of early PVR.